Women’s Participation in Labor Force in Sub-Saharan Africa (SSA): A Review of Determinants and Impacts - Victoria Matatio Elia Guli; Nigatu Regassa Geda (Archives of Current Research International, 2021)
Background: In the last few decades, there has been a significant increase in women’s participation in gainful employment in Sub-Saharan Africa (SSA). This scooping review has primarily aimed at assessing the key determinants and effects of women’s involvement in the labor force in SSA. Methods: The authors did the review based on 19 articles selected from PubMed and goggle search. The selection considered only those published in the last 15 years, conducted based on large sample from Sub-Saharan African countries, and those exclusively related to women’s Labor Force Participation (LFP). More than 80% of the reviewed studies (16 of the 19) employed a cross-sectional study design with quantitative approaches. Results: The review witnessed that women’s labor force participation in SSA is determined by various individual, household, and community characteristics. Women with lower fertility, living in poor economic condition (low wealth quantiles), and those with above primary education were more likely to participate in gainful employment. Other demographic factors explaining why some women participate in the labor force more often than others include women’s age, marital status, number of under-five children, household size, and headship. Among the community variables, living in areas with better infrastructure (transport and communication) increased the likelihood of women’s participation in gainful employment. Nearly all studies showed significant positive impacts of women’s labor force participation on several domains of women’s life and household well-being, such as on women’s nutrition, childcare, and health service utilization. Conclusion: The review implies that despite concerns about some adverse impacts of women’s participation in gainful employment (such as on childcare), most of the studies indicated positive effects of LFP on women’s and children’s health, nutrition, and overall household well-being in SSA.